SANKSI MEMPEKERJAKAN ANAK DI BAWAH UMUR BERDASARKAN UNDANG- UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DI KOTA SORONG - Murary, Weron; M, Novalin; Syauta, Syauta; Jarangga, Zefanya Caroline (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The problem of child labor is also regulated in Article 1 of the Law Employment Number 25 of 1997, as well as determining the age limit of a person children who can be employed, both for boys and for children girls. But until now the problem of child labor is still there into controversy. It can be said that, the problem of child labor is the classic problem of child protection. Because hiring a underage children is something that violates children's rights, because exploitation of child laborers will always have a negative impact on them, collectively physical, emotional, and social.This research was conducted from June to August 2020 at the Women Empowermentand Child Protection Office and at the Sorong City Manpower Office.This study aims to determine how child laborers are treated, as well as how sanctionsare given to those who employ underage children and to find out all the causes of childlabor in Sorong City.Data collection conducted by the author is by means of interviews, observation and alsoby literature study. Mean while, the data collected by the authors were processed using qualitative data analysis methods